frugivory and seed dispersal by lizards in Brazilian ecosystems: a review - Santos, Norma Érica Freire dos; Dias, Uêdija Natalí Silva; Bezerra, Juliana Karla; Silva, Carla Daiane Andrade da; Ribeiro, Leonardo Barros (Revista Nordestina de Zoologia, 2012)
The aim of this study was to gather information available in the literature about frugivory and seed dispersal in the brazilian ecosystems, highlighting the importance of the lizards in these events. To find reports of frugivory and seed dispersal were consulted articles published in the last two decades. After the literature review, it was possible to account for 65 articles published in the past 19 years. These studies described the frugivore behavior and/or seed dispersal, mostly for birds (32.4%), mammals (31.0%), and lizards (29.6%). However, more effort has been invested in attempting to identify the plant species eaten by birds and mammals. Ecosystems that have been most studied in the aspect of relations of frugivory and seed dispersal are the Atlantic Forest (64.6%), Cerrado (18.5%), Caatinga (9.2%) and the Amazon Forest (7.7%). For research with lizards, 57.14% of works were performed in the Atlantic Forest, 23.81% in the Caatinga, and 19.05% in the Amazon Forest.